A Study on the Nested Rings CME Structure Observed by the WISPR Imager Onboard Parker Solar Probe - Shaheda Begum Shaik; Mark G. Linton; Sarah E. Gibson; Phillip Hess; Robin C. Colaninno; Guillermo Stenborg; Carlos R. Braga; Erika Palmerio (The Astrophysical Journal)
Despite the significance of coronal mass ejections (CMEs) in space weather, a comprehensive understanding of their interior morphology remains a scientific challenge, particularly with the advent of many state-of-the-art solar missions such as Parker Solar Probe (Parker) and Solar Orbiter (SO). In this study, we present an analysis of a complex CME as observed by the Wide-Field Imager for Solar PRobe (WISPR) heliospheric imager during Parker’s seventh solar encounter. The CME morphology does not fully conform with the general three-part density structure, exhibiting a front and core not significantly bright, with a highly structured overall configuration. In particular, its morphology reveals nonconcentric nested rings, which we argue are a signature of the embedded helical magnetic flux rope of the CME. For that, we analyze the morphological and kinematical properties of the nested density structures and demonstrate that they outline the projection of the three-dimensional structure of the flux rope as it crosses the lines of sight of the WISPR imager, thereby revealing the magnetic field geometry. Comparison of observations from various viewpoints suggests that the CME substructures can be discerned owing to the ideal viewing perspective, close proximity, and spatial resolution of the observing instrument.